The "Real Delinquents" and the Others: Professional Hierarchization of Youth Offenders in a “Closed Educational Center” - Carlos, Rita (Swiss Journal of Sociocultural Anthropology, 2020)
This article presents an analysis of the day-to-day practices of agents duly of the State at the end of the penal chain in the context of increasing hybridization of public policy. Faced with the challenges posed by the diversification of adolescent profiles in French “closed educational centers”, the educators categorize and hierarchize these youths on the basis of their previous institutional trajectories. Those labeled “handicapped”, “foreign” or “radicalized” are deemed unfit for professional reintegration, and are subjected to different levels of coercion than the “real delinquents”. These labels reveal the staff’s resistance to the transformation of their mission, which they perceive as an obstacle both to their effectiveness and their professional recognition. The use of these categories of action allows educators and the institution to transfer the blame of educational failures to those who suffer from them.